f(x)*f(-x)=f(x)+f(-x)

Simple and best practice solution for f(x)*f(-x)=f(x)+f(-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x)*f(-x)=f(x)+f(-x) equation:


Simplifying
f(x) * f(-1x) = f(x) + f(-1x)

Remove parenthesis around (-1x)
f * x * f * -1x = f(x) + f(-1x)

Reorder the terms for easier multiplication:
-1f * x * f * x = f(x) + f(-1x)

Multiply f * x
-1fx * f * x = f(x) + f(-1x)

Multiply fx * f
-1f2x * x = f(x) + f(-1x)

Multiply f2x * x
-1f2x2 = f(x) + f(-1x)

Multiply f * x
-1f2x2 = fx + f(-1x)

Remove parenthesis around (-1x)
-1f2x2 = fx + f * -1x

Reorder the terms for easier multiplication:
-1f2x2 = fx + -1f * x

Multiply f * x
-1f2x2 = fx + -1fx

Combine like terms: fx + -1fx = 0
-1f2x2 = 0

Solving
-1f2x2 = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '-1'.
f2x2 = 0

Simplifying
f2x2 = 0

The solution to this equation could not be determined.

See similar equations:

| f(x)Xf(-x)=f(x)+f(-x) | | 5y=7x+5 | | 12y+18=102 | | 10y=8x+6 | | 2x^3+4x^2-36x+15=0 | | 10t^2+29t-21=0 | | 34X=4+2 | | 4(x-3)-2x=10-2(3x-1) | | 10y=5x+2 | | 4(x-3)-2x=10-2(3x-1) | | 5*t+6(1.8-t)=6 | | -6x+4y=11 | | 6*t+8*(1-t)=7 | | 11=6+4-4 | | -18+5x=5x-18 | | (2x-5)(x^2-7x+12)=0 | | 3x=12+4 | | 94+7x=102+6x | | 3.6(4+5x)-3.4=11 | | .9x+.2*90=.8(90+x) | | 2x+4(x-20)=220 | | 10y=6x-10 | | 9x^2-2x+5=0 | | 4x^2-8x+4=56 | | 4y-5+y+26=7+5y+23-3y | | 2m+3n=19 | | 53+6x=61+4x | | X+0.04x=31.2 | | 1.5x+3.7=3.4x-2 | | 4x+4(x-20)=424 | | 4cos(3x)=3 | | 20x+7=2x+25 |

Equations solver categories